Strategi Perekayasaan Subak Sembung sebagai Daya Tarik Wisata di Perkotaan - PUTRI, NI LUH MADE AYU YULIANTARI; SURYAWARDANI, I G.A. OKA; DIARTA, I KETUT SURYA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
Subak Sembung Development Strategy As A Tourist Attraction In The Urban Area Tourism development in Bali is culture-based tourism. One of them is Subak Sembung Ecotourism which is located in Peguyangan Village, North Denpasar District, Denpasar Municiplity. Its strategic location in the city center makes Subak Sembung face challenges in land conversion. Development efforts needed to make Subak Sembung a tourist attraction as well as a traditional organization in agriculture. The purpose of this study was to identify the strengths, weaknesses, opportunities, and threats of Subak Sembung, formulate alternative strategies, and determine priority strategies to develop Subak Sembung as a tourist attraction in urban areas. The results of the SWOT matrix produced several alternative strategies, namely market expansion, collaboration with government and external entrepreneurs, developing agricultural-based tourist attractions, holding promotions, arousing agricultural activities and religious rituals, development efforts that were in accordance with the awig-awig of subak, forming management bodies of ecotourism, and selective in developing tourism facilities. The priority strategy based on QSPM analysis was to establish an ecotourism management body so that Subak Sembung could be developed with better facilities. Subak member together with the government and other stakeholders must take advantage of the opportunities and strengths they have in order to minimize the weaknesses and threats faced by Subak Sembung. Based on the results of the study, the suggestion that can be made is to form a more creative ecotourism management body so that the appreciation and activities of the community can be developed for the sustainability of Ecotourism in Subak Sembung.